Development of Teaching Materials Based on Discovery Learning on Science Lessons With Adictive and Psychotropic Themes in Middle School - Astuti Widodo, Riza Puji; Lisdiana, Lisdiana; Nuswowati, Murbangun (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
This study aims to determine the feasibility, validity and effectiveness of science learning materials based on discovery learning to improve learning outcomes and student curiosity. This research is a Research and Development (R&D) study. The model used in this study is the 4D model consists of four stages of development, namely Define (defining), Design (design), Develop (development), and Disseminate (spread). The method used in this research is observation, questionnaire, test, and documentation. The feasibility of teaching materials is obtained from the response of students and teachers to teaching materials. The validity of teaching materials is obtained from the validation of media and material experts. Effectiveness is measured by student learning outcomes and increased curiosity. The results of the study showed that discovery learning based science materials were developed appropriate, valid and effective to improve learning outcomes and students' curiosity. The N-Gain results were 0.71 with a high level of achievement, and the percentage of students' increasing curiosity attitudes was 70.12%, 79.69% and 82.03%. The results of the study concluded that science learning materials based on discovery learning were developed effectively to improve learning outcomes and students' curiosity.